Diversity of fungal spores associated with Rhizospheric soil of Juniper Communis, Juniper Recurva and Juniper Macropoda of cold deserts of Himachal Pradesh - AYUSH BANTA; SUJATA BHATTACHARYA; VIJAY CHAUHAN (International Journal of Pharma and Bio Sciences, 2018)
The rhizosphere generally comprises of various types of microorganisms like bacteria and fungus. The overall performance of the plants including physiological performance, crop quality as well as the crop productivity totally depends upon the rhizosphere. Among the rhizosphere components, arbuscular mycorrhizae fungi (AMF) is one of the most common types of symbiotic associations between some rhizosphere microorganisms and root of higher plants. The present study was conducted to investigate the comparative analysis of fungal status in rhizosphere of Juniper communis, Juniper macropoda and Juniper recurva from three selected sites in Kinnaur (H.P.). Microflora plays a very important role in maintaining balance in life. Diversity of fungal spores were seen and these were isolated and identified during the investigation. Glomus, Acaulospora and Gigaspora gigantea are dominating genera and also included there species. The whole spores are common native of cold deserts and it has been seen that with the increase in the altitude, spore density decreases. Various biochemical tests have been done to differentiate the soil samples from one another.